THE VARIATION OF PROTEIN CONTENT IN MAIZE GRAINS IN RELATION TO THE FERTILIZATION LEVEL - Alina Laura AGAPIE; Florin SALA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study analyzed the variation of protein content in maize grains under the influence of mineral fertilization. The experiment was organised at the Agricultural Research and Development Station Lovrin, Timis County, Romania. The study was carried out under the conditions of the 2019-2020 agricultural years, on a chernozem type soil with medium fertility. The corn hybrid DEKALB 4541, non-irrigated culture system, was cultivated. Fertilization was done with nitrogen (ammonium nitrate, doses between 0-200 kg ha-1 N, active substance) and phosphorus (concentrated superphosphate, doses between 0-160 kg ha-1 P2O5, active substances). The combination of the two fertilizers resulted in 25 fertilization variants (V0 – control, to V25). The protein content (Pro, %) recorded values between 5.5±0.62% and 9.5±0.73%. The variation of the protein content under the influence of N, on each level of P, was described by polynomial equations of the 2nd degree, under statistical safety conditions (R2=0.854 to R2=0.975). The regression analysis facilitated the description of the protein content variation (Pro, %) in relation to N and P as a direct action and interaction, and the generation of 3D graphic models and in the form of isoquants, under statistical safety conditions. The cluster analysis facilitated the grouping of the variants based on the Euclidean distances, in relation to the similarity for the protein content values generated, in conditions of statistical safety condition (Coph. corr. =0.872).